Target Zones and Interest Rate Variability - Svensson, Lars (IMF Working Papers; Working Paper ;, 1990)
The trade-off between interest rate variability and the width of an exchange rate target zone is examined, using the regulated Brownian motion model of target zones. The interest rate differential's asymptotic (unconditional) variability is increasing in the exchange rate band for narrow bands; whereas it is slowly decreasing for wide bands. The interest rate differential's instantaneous (conditional) variability is decreasing in the exchange rate band. The model is extended to include a realignment/devaluation risk, as well as an endogenous exchange rate risk premium. The risk premium is small for reasonable parameter values.